The ubiquitin proteasomal system: a potential target for the management of Alzheimer's disease. Issue 7 (29th March 2016) - Gadhave, Kundlik; Bolshette, Nityanand; Ahire, Ashutosh; Pardeshi, Rohit; Thakur, Krishan; Trandafir, Cristiana; Istrate, Alexandru; Ahmed, Sahabuddin; Lahkar, Mangala; Muresanu, Dafin F.; Balea, Maria
Abstract: The cellular quality control system degrades abnormal or misfolded proteins and consists of three different mechanisms: the ubiquitin proteasomal system (UPS), autophagy and molecular chaperones. Any disturbance in this system causes proteins to accumulate, resulting in neurodegenerative diseases such as amyotrophic lateral sclerosis, Alzheimer's disease (AD), Parkinson's disease, Huntington's disease and prion or polyglutamine diseases. Alzheimer's disease is currently one of the most common age‐related neurodegenerative diseases. However, its exact cause and pathogenesis are unknown. Currently approved medications for AD provide symptomatic relief; however, they fail to influence disease progression. Moreover, the components of the cellular quality control system represent an important focus for the development of targeted and potent therapies for managing AD. This review aims to evaluate whether existing evidence supports the hypothesis that UPS impairment causes the early pathogenesis of neurodegenerative disorders. The first part presents basic information about the UPS and its molecular components. The next part explains how the UPS is involved in neurodegenerative disorders. Finally, we emphasize how the UPS influences the management of AD. This review may help in the design of future UPS‐related therapies for AD.